METHODS OF ASSESSING KNOWLEDGE OF THE RUSSIAN LANGUAGE IN PUPILS OF SCHOOLS WITH UZBEK LANGUAGE OF INSTRUCTION - Касымова Ф.С. (Web of Journals Publishing, 2024)
This article discusses the issues of assessing the knowledge of pupils in the Russian language in schools with Uzbek as the language of instruction; the roles of using methods and techniques of new pedagogical technologies in the classroom are determined on the example of the evaluation sheet.
Keywords: cretic thinking, differentiated evaluation, motivation, types of control, evaluation sheet.